Respuesta :

Answer: -3

Concept:

Here, we need to understand the idea of evaluation.  

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given information

x= -3

Given expression

5x - 4 [7 + (2x - 4)]

Substitute x value into the expression

=5(-3) - 4 [7 + (2(-3) - 4)]

Simplify by multiplication

=-15 - 4 [7 + (-6 - 4)]

Simplify value in parentheses

=-15 - 4 [7 + (-10)]

Simplify value in bracket

=-15 - 4 [-3]

Simplify by multiplication

=-15 - (-12)

=-15 + 12

=[tex]\boxed{-3}[/tex]

Hope this helps!! :)

Please let me know if you have any questions

5×(-3)-4{7+[2×(-3)-4]}
-15-4[7+(-6-4)]
=-15-4[7+(-10)]
=-15-4(7-10)
=-15-4×(-3)
=-15+12
=-3

Hope my answer helped u :)